Bruteforce In The Hydra Process And Telnet Service Using The Naïve Bayes Method: Bruteforce In The Hydra Process And Telnet Service Using The Naïve Bayes Method - Tarisno Amijoyo; Rusydi Umar; Anton Yudhana (Jurnal Mantik, 2020)
Internet technology is increasingly developing, in accordance with the needs of an increasingly millennial society. The growth of internet technology has been accompanied by an increasing variety of attack techniques aimed at the media. BruteForce is one of the techniques of attack (hacking) against the internet network by hacking passwords from users who are active or inactive at that time. Through a process with a small application such as Hydra accompanied by telnet service, then hacking techniques with BruteForce can be run, to attack an internet network. The Hydra process and the telnet service referred to in the study are those that included a "wordlist" file containing user information and password data. The count to detect, whether entering the network is a BruteForce attack or just normal / normal network traffic, can be done with the Naïve Bayes theorem or the Naïve Bayes method. The purpose of the Naïve Bayes method, is to be able to distinguish and classify, which is attack traffic, which is normal / normal network traffic. The reason for using the Naïve Bayes method is that the formulation in this method is easier to calculate when classifying the type of network traffic. From the results of the classification, it can be used as a reference for a network administrator to be more careful and better understand how to protect and prevent attacks from hackers, especially those who use BruteForce hacking techniques. The hope of this research, can be understood and understood so that it can be very easy for a network administrator to distinguish between the two traffic on the network, whether it is attack traffic and / or normal / normal traffic that is through the display on the Wireshark tool.